Rainbow Valley [Dúhové údolie anglicky] / book 7 - Montgomery, Lucy Maud, 1874-1942 (Leicester : Fox Eye Publishing Ltd., 2022)
There was a little unfailing spring, always icy cold and crystal pure, in a certain birch-screened hollow of Rainbow Valley in the lower corner near the marsh.
Contains a short biography and bibliography of L. M. Montgomery.
Keywords: Stories for girls; Children's and juvenile literature; literatúra pre deti a mládež; cudzojazyčná literatúra; čítanie je IN (11+)